Exploring the utility of DNA barcoding in species delimitation of Polypedilum (Tripodura) non-biting midges (Diptera: Chironomidae) - Song, Chao; Wang, Qian; Zhang, Ruilei; Sun, Bingjiao; Wang, Xinhua (Zootaxa, 2016)
In this study, we tested the utility of the mitochondrial gene cytochrome c oxidase subunit 1 (CO1) as the barcode region to deal with taxonomical problems of Polypedilum (Tripodura) non-biting midges (Diptera: Chironomidae). The 114 DNA barcodes representing 27 morphospecies are divided into 33 well separated clusters based on both Neighbor Joining and Maximum Likelihood methods. DNA barcodes revealed an 82% success rate in matching with morphospecies. The selected DNA barcode data support 37–64 operational taxonomic units (OTUs) based on the methods of Automatic Barcode Gap Discovery (ABGD) and Poisson Tree Process (PTP). Furthermore, a priori species based on consistent phenotypic variations were attested by molecular analysis, and a taxonomical misidentification of barcode sequences from GenBank was found. We could not observe a distinct barcode gap but an overlap ranged from 9–12%. Our results supported DNA barcoding as an ideal method to detect cryptic species, delimit sibling species, and associate different life stages in non-biting midges.